WATER AVAILABILITY INFLUENCE ON YIELD AND WATER CONSUMPTION OF POTATO ON THE BLACK-EARTH SOILS OF VOLGOGRAD REGION - A. A. Novikov (Научный журнал Российского НИИ проблем мелиорации, 2020)
Purpose: to determine the water availability impact on the growth, development, yield and water consumption characteristics of spring planted potatoes. Materials and methods: the research was conducted on chernozem soils of Volgograd region. The impact of water availability on the growth, development, yield and water consumption of potatoes was studied. Different water availability was created by changing the calculated water application rate and irrigation rate (control) by increasing by 20 % and decreasing by 20 and 40 %. The experiments were laid out according to B. A. Dospekhov (1985), observations and studies were carried out according to the methodology of All-Russian Research Institute of Irrigated Agriculture named after V. N. Pleshakov (1983). Mathematical processing of experimental data was performed using Microsoft Office Excel 2007. Results: it was found that morphological indicators changed under the influence of different water availability: in option 2, the plants had the biggest height (0.74 m) and leaf area in the budding and flowering phase (30.9 and 30.1 thousand m²/ha), but the higher water availability in option 2 did not contribute to the formation of a larger oven dry mass. Productivity of marketable tubers was higher (58.8 t/ha) in option 1 versus 55.9 t per ha in option 2. It turned out to be lower than in the control, due to the higher percentage of tuber damage by phytophthora, although the difference in yield in 2016 and 2017 was within the least significant difference, and in 2015 was significant – more than the LSD. Conclusions: a decrease in the irrigation rate by 20 % in option 3 and by 40 % in option 4 led to a decrease in yield to 53.1 and 43.7 t/ha, respectively, but when the irrigation rate decreases by 20 % in option 3, the yield decreases only 9.7 %, and a decrease in irrigation rate by 40 % leads to a decrease in productivity by 25.6 %, i. e. one can talk about water resources saving per unit of output.